PENGEMBANGAN LKS BERBASIS PROBLEM BASED LEARNING MATERI PENGUKURAN KELAS X SMA - Siti Fatimah; Chandra Ertikanto; Wayan Suana (Jurnal Pembelajaran Fisika, 2014)
Students worksheet is a media supporting for learning. Based on need identification, media which is used as learning source in Muhammadiyah 2 Senior High School in Bandar Lampung was only student’s book only. The objective of this research was to produce problem based learning students worksheet of measurement material for grade X of Senior High School. The development method was adapted from steps in research and development according to Suyanto and Sartinem which included seven stages of development. The test results from user’s responses showed scores of 3,41 with very good category for attractiveness aspect, 3,31 with very good category for easiness aspect, and 3,48 with very good category for usefulness aspect. The effectiveness of test result showed 77,5% with 70 students accomplished least minimum accomplishment. The conclusion was that the students worksheet was proper and effective to use as a learning media.LKS merupakan sebuah media penunjang pembelajaran. Berdasarkan identifikasi kebutuhan, media yang digunakan sebagai sumber belajar di SMA Muhammadiyah 2 Bandar Lampung hanya buku siswa. Tujuan dari penelitian ini adalah menghasilkan LKS berbasis problem based learning materi pengukuran siswa kelas X SMA Muhammadiyah 2 Bandar Lampung. Metode pengembangan diadaptasi dari langkah-langkah penelitian dan pengembangan menurut Suyanto dan Sartinem, yang meliputi tujuh tahapan pengembangan. Hasil uji coba terhadap respon pengguna untuk aspek kemenarikan diperoleh skor 3,41 dengan kategori sangat baik, aspek kemudahan diperoleh skor 3,31 dengan kategori sangat baik, untuk aspek kebermanfaatan diperoleh skor 3,48 dengan kategori sangat baik. Sementara itu, hasil uji efektivitas mencapai 77,5% siswa tuntas KKM 70. Dengan demikian, LKS layak dan efektif digunakan sebagai media pembelajaran.Kata kunci: LKS, pengembangan, problem based learning.